Aluminum alloy coated plate for can lids

The aluminum alloy coating plate for can lids, with its optimized composition and subgrain structure, addresses the issue of cracking during rivet molding of thin sheets, ensuring high moldability and strength.

JP7663363B2Active Publication Date: 2025-04-16KOBE STEEL LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021010403
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-26
Publication Date
2025-04-16
Estimated Expiration
2041-01-26

AI Technical Summary

Technical Problem

Conventional aluminum alloy sheets for can lids experience cracks during rivet molding when thinned to about 0.2 mm, leading to potential leaks and reduced productivity in direct-through processes.

Method used

An aluminum alloy coating plate for can lids is developed, containing specific compositions of Si, Fe, Cu, Mn, Mg, and a resin layer, with a structure featuring 45 or more subgrains in a 50 nm thick region at the center of the plate thickness, enhancing formability and strength.

Benefits of technology

The solution provides high rivet moldability even at thinner gauges, maintaining sufficient strength and preventing cracks during the rivet molding process, thereby improving productivity and leak resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663363000002
    Figure 0007663363000002
  • Figure 0007663363000003
    Figure 0007663363000003
  • Figure 0007663363000004
    Figure 0007663363000004
Patent Text Reader

Abstract

To provide an aluminum alloy coated sheet for a can lid having high rivet moldability even when thinned.SOLUTION: An aluminum alloy coated sheet for a can lid includes an aluminum alloy sheet which contains 0.05 mass% or more and 0.40 mass% or less Si, 0.05 mass% or more and 0.50 mass% or less Fe, 0.01 mass% or more and 0.30 mass% or less Cu, 0.10 mass% or more and 0.60 mass% or less Mn, 4.0 mass% or more and 6.0 mass% or less Mg, and the balance Al with inevitable impurities, and a resin layer. In the aluminum alloy coated sheet for the can lid, a tissue in a region of 50 nm thickness in both thickness directions from a sheet thickness center on a surface parallel to a rolled surface has 45 pieces or more of sub-grains in total in a region of 205×10-12 m2 observed by a transmission type electron microscope of 50,000 magnifications.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coated aluminum alloy sheet for can ends. [Background technology]

[0002] Two-piece aluminum cans consisting of a cylindrical body with a bottom and a lid are widely used as beverage packaging containers. The riveting process is the most severe forming process in forming the lid of a two-piece aluminum can. If fine breaks or cracks occur in this process, the risk of leakage of the contents increases, so intermediate annealed materials, which are subjected to intermediate annealing between cold rolling processes with excellent formability, have been used in the past. However, in recent years, from the viewpoint of improving productivity, there has been a demand to manufacture cold-rolled materials with improved formability in a process that does not perform intermediate annealing (hereinafter also referred to as a direct process).

[0003] Regarding aluminum alloy sheets for can ends, technologies have been developed that ensure formability even in a direct pass process. For example, Patent Document 1 describes an aluminum alloy sheet for can ends that has a texture in which the cube orientation density on the sheet surface is 1.5 times or more that of a random orientation sample, and has excellent bending workability. Patent Document 2 describes an aluminum alloy sheet for can ends that has excellent strength and formability, with a solute Mg ratio of 80% or more and a subgrain area ratio of 10% to 90%. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-150043 A [Patent Document 2] JP 2016-79501 ​​A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in recent years, when can end materials have become thinner (for example, to a thickness of about 0.2 mm), conventional aluminum alloy sheets for can ends that are processed through a direct process may crack during rivet forming. An object of the present invention is to provide an aluminum alloy coated sheet for can ends that has high rivet formability even when it is thinner. [Means for solving the problem]

[0006] The coated aluminum alloy sheet for can ends according to the present invention comprises an aluminum alloy sheet containing 0.05% by mass to 0.40% by mass of Si, 0.05% by mass to 0.50% by mass of Fe, 0.01% by mass to 0.30% by mass of Cu, 0.10% by mass to 0.60% by mass of Mn, 4.0% by mass to 6.0% by mass of Mg, with the balance being Al and unavoidable impurities, and a resin layer. The coated aluminum alloy sheet for can ends has a structure of 205×10 microns in a region 50 nm thick in both thickness directions from the center of the sheet thickness in a plane parallel to the rolling surface, as observed by a transmission electron microscope at 50,000 magnification. -12 m 2 The grain size is 45 or more subgrains in the area. Effect of the Invention

[0007] According to the present invention, it is possible to provide a coated aluminum alloy sheet for can ends which has high rivet formability even when made thin. [Brief description of the drawings]

[0008] [Figure 1] 1 is an example of a transmission electron microscope image of the structure of an aluminum alloy plate. [Diagram 2] FIG. 4 is a schematic cross-sectional view illustrating a method for measuring the limit overhang height. [Diagram 3] 1 is a graph showing the relationship between the limit overhang height and the final winding temperature. [Figure 4] 1 is a graph showing the relationship between the critical overhang height and the number of subgrains. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, an aluminum alloy coated sheet for can lids according to one embodiment of the present invention will be described. However, the embodiment shown below is merely an example for embodying the technical idea of ​​the present invention, and the present invention is not limited to the following embodiment. The size and positional relationship of the members shown in each drawing may be exaggerated for clarity of explanation. In this specification, the term "process" includes not only an independent process, but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process is achieved. Furthermore, the content of each component in the composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified.

[0010] Aluminum alloy coated plate for can lids The aluminum alloy coated sheet for can lids according to one embodiment of the present invention comprises an aluminum alloy sheet and a resin layer provided on one or both sides of the aluminum alloy sheet. The aluminum alloy coated sheet for can lids, after baking treatment, has a structure of a region 50 nm thick in both thickness directions from the center of the sheet thickness (hereinafter, sometimes referred to as the center of the sheet thickness) observed by a transmission electron microscope at 50,000 magnifications, which is 205×10 -12 m 2 The grain size is 45 or more subgrains in the area.

[0011] The aluminum alloy coated sheet for can ends, after being baked and finished, must satisfy the characteristics required for can ends, such as formability to withstand lid processing, pressure resistance to withstand the internal pressure after filling with a beverage, and openability for normal and easy can opening. In the aluminum alloy coated sheet for can ends according to one embodiment of the present invention, the number of subgrains contained in the structure in the center of the sheet thickness after being baked and finished after cold rolling is increased to a predetermined value or more, thereby improving formability, particularly rivet formability, while maintaining strength.

[0012] Aluminum Alloy Composition The aluminum alloy sheet constituting the aluminum alloy coated sheet for can lids is made of, for example, an Al-Mg alloy, for example, a general JIS alloy such as 5182.

[0013] Specifically, the aluminum alloy plate contains Si: 0.05% by mass to 0.40% by mass, Fe: 0.05% by mass to 0.50% by mass, Cu: 0.01% by mass to 0.30% by mass, Mn: 0.10% by mass to 0.60% by mass, Mg: 4.0% by mass to 6.0% by mass, and the balance is Al and inevitable impurities. The content of each component contained in the aluminum alloy plate and the reason for limiting the content will be described below.

[0014] (Si: 0.05 mass% or more and 0.40 mass% or less) If the Si content is less than 0.05% by mass, high-purity aluminum ingots are required during casting, which increases costs. If the Si content exceeds 0.40% by mass, a large number of intermetallic compounds are formed during casting and hot rolling, which promotes the generation and propagation of cracks, reducing the can-opening load and making unintended can-opening more likely. The Si content is preferably 0.30% by mass or less, and more preferably 0.20% by mass or less. The Si content is preferably 0.06% by mass or more.

[0015] (Fe: 0.05 mass% or more and 0.50 mass% or less) If the Fe content is less than 0.05% by mass, high-purity aluminum ingot is required during casting, which increases costs. On the other hand, if the Fe content exceeds 0.50% by mass, the amount of Al-Fe-Mn intermetallic compounds increases, and many intermetallic compounds are formed during casting and hot rolling, which promotes the generation and propagation of cracks, reducing the can opening load and making unintended can opening more likely to occur. The Fe content is preferably 0.10% by mass or more, more preferably 0.15% by mass or more. The Fe content is preferably 0.40% by mass or less, more preferably 0.35% by mass or less, and even more preferably 0.30% by mass or less.

[0016] (Cu: 0.01 mass% or more and 0.30 mass% or less) If the Cu content is less than 0.01% by mass, the strength is insufficient, and the pressure resistance of the lid is insufficient. On the other hand, if the Cu content exceeds 0.30% by mass, the strength becomes too high, and the rivet formability decreases. The Cu content is preferably 0.02% by mass or more, and more preferably 0.03% by mass or more. In addition, the Cu content is preferably 0.25% by mass or less, more preferably 0.20% by mass or less, and even more preferably 0.15% by mass or less.

[0017] (Mn: 0.10 mass% or more and 0.60 mass% or less) If the Mn content is less than 0.10% by mass, the strength is insufficient, and the pressure resistance of the lid is insufficient. On the other hand, if the Mn content exceeds 0.60% by mass, the strength becomes too high and the amount of Al-Fe-Mn intermetallic compounds increases, which reduces the rivet formability. The Mn content is preferably 0.20% by mass or more. The Mn content is preferably 0.55% by mass or less, and more preferably 0.50% by mass or less.

[0018] (Mg: 4.0 mass% or more and 6.0 mass% or less) If the Mg content is less than 4.0% by mass, the strength is insufficient, and the pressure resistance of the lid is insufficient. In addition, the work hardening ability of the aluminum alloy coated plate is insufficient, and necking is likely to occur during rivet forming. On the other hand, if the Mg content exceeds 6.0% by mass, the strength becomes excessive and the rivet formability decreases. The Mg content is preferably 4.5% by mass or more. In addition, the Mg content is preferably 5.5% by mass or less, and more preferably 5.0% by mass or less.

[0019] (Ti: 0.1% by mass or less) The aluminum alloy plate may contain Ti. Ti is added as necessary for the purpose of refining the ingot crystal grains. Refining the ingot structure during casting improves castability and enables high-speed casting. This effect can be obtained by adding 0.01 mass% or more. On the other hand, if the Ti content exceeds 0.1 mass%, coarse compounds are formed, causing a decrease in rivet formability. Therefore, the Ti content in the aluminum alloy may be limited within the above range. When Ti is added, for example, an ingot refiner (Al-Ti-B) with a mass ratio of Ti and B of 5:1 is added. Since it is added to the molten metal before casting in the form of a waffle or rod, B is inevitably added according to the content ratio. The Ti content may be preferably 0.08 mass% or less, more preferably 0.06 mass% or less.

[0020] (Cr: 0.1% by mass or less) The aluminum alloy plate may contain Cr. If the Cr content is 0.1 mass% or less, it does not affect the material properties of the aluminum alloy plate. Although Cr is an inevitable impurity, in order to reduce costs, Cr can be actively added within the above range, for example, by increasing the scrap (scrap containing a large amount of Cr) blending rate in the raw material. The Cr content may be preferably 0.05 mass% or less.

[0021] As long as the Ti and Cr do not exceed the upper limit values ​​described above, not only when the aluminum alloy contains one or more kinds, i.e., only one kind, but also when the aluminum alloy contains two or more kinds, the effects of the present invention are naturally suppressed from being hindered.

[0022] (balance: Al and unavoidable impurities) The aluminum alloy plate may contain inevitable impurities in addition to Al and the above alloy components. Examples of inevitable impurities include Zn, Zr, B, V, Na, Ca, Ni, In, Sn, and Ga. The allowable content of inevitable impurities may be, for example, 0.3 mass% or less for Zr, preferably 0.1 mass% or less, and more preferably 0.05 mass% or less. For elements other than Zr, each may be, for example, 0.05 mass% or less and a total of 0.15 mass% or less. If within the above range, the effects of the present invention are suppressed from being hindered even when the elements are added, not limited to when they are contained as inevitable impurities.

[0023] The thickness of the aluminum alloy plate constituting the aluminum alloy coated plate for can ends may be, for example, 0.15 mm or more and 0.30 mm or less.

[0024] Aluminum alloy plate structure In one embodiment of the present invention, the aluminum alloy sheet has the above-mentioned alloy composition, is cold rolled without intermediate annealing, and is then heat-treated by baking paint treatment, and has a structure having 45 or more subgrains in a predetermined region in the center of the sheet thickness. By making the aluminum alloy sheet have a structure having a predetermined number of subgrains or more, it is possible to solve a problem that has been difficult to solve in the past, that is, to improve rivet formability while maintaining strength. The subgrains possessed by the aluminum alloy sheet are 205×10 in a 100 nm thickness in the center of the sheet thickness in a plane parallel to the rolling surface. -12 m 2 They are counted by observing them under a transmission electron microscope (TEM) at 50,000 magnification.

[0025] Subgrains, also known as subcrystal grains, are small, irregular grains that arise when a material (structure) into which dislocations have been introduced by cold rolling or other methods undergoes recovery to a lower energy structure under a given temperature, time, and strain.

[0026] That is, in the case of coated aluminum alloy sheet for can ends, subgrains with sharp boundaries are formed when dislocations in dislocation-dense regions such as dislocation cell walls and deformation bands introduced by cold rolling coalesce and annihilate and rearrange. When many dislocation-dense regions are formed, the probability that they will coalesce and annihilate with newly arriving dislocations increases, lowering the work-hardening index (n-value), but the formation of a subgrain structure improves the work-hardening index (n-value). An improved work-hardening index (n-value) improves uniform deformability, and therefore improves rivet formability. For this reason, the more subgrains there are, the better the rivet formability.

[0027] An example of an observed subgrain is shown in Figure 1. Figure 1 is an example of a transmission electron microscope (TEM) image at 50,000 times magnification. Subgrains 20 are formed from dislocation-dense regions 10, and the subgrains 20 are identified within the crystal grains as small, individual, irregular grains with a sharp (clear and distinct) outer edge shape that is the boundary and few internal dislocations.

[0028] In this way, the number of individual subgrains can be counted in the observation field of the transmission electron microscope. It is also possible to measure the area ratio of the subgrains instead of the number of subgrains present in a given observation field. However, in that case, the size of the subgrains is not taken into consideration, so a high subgrain area ratio can be obtained even in the case of a coarse subgrain structure. Since a coarse subgrain structure has a lower dislocation density than a fine subgrain structure, the strength is reduced and the strength required for a can lid cannot be obtained.

[0029] Therefore, in one embodiment, the size of the subgrain may be, for example, 1500 nm or less, preferably 1000 nm or less, as the equivalent circle diameter. The lower limit of the equivalent circle diameter of the subgrain may be, for example, 50 nm or more. The equivalent circle diameter is calculated by measuring the boundary length of the subgrain and calculating it as the diameter of a circle having the same length as the boundary length.

[0030] In one embodiment, the number of subgrains in a predetermined region in the center of the sheet thickness of the aluminum alloy sheet constituting the aluminum alloy coated sheet for can ends may be 45 or more, preferably 60 or more, and more preferably 100 or more. The upper limit of the number of subgrains may be, for example, 600 or less.

[0031] When the number of subgrains in a predetermined region in the thickness center of an aluminum alloy sheet is as small as less than 45, the aluminum alloy sheet has high strength, but on the other hand, it may not be possible to achieve both excellent rivet formability and high strength at the same time, i.e., it may not be possible to increase the strength of the aluminum alloy coated sheet for can ends while maintaining the formability.

[0032] The aluminum alloy coated sheet for can lids has excellent strength and formability. The sheet strength of the aluminum alloy coated sheet for can lids may be, for example, 300 MPa or more, preferably 320 MPa or more, more preferably 330 MPa or more, and even more preferably 340 MPa or more, as 0.2% proof stress. The upper limit of the sheet strength of the aluminum alloy coated sheet for can lids is, for example, 390 MPa or less, as 0.2% proof stress. The formability of the aluminum alloy coated sheet for can lids can be evaluated, for example, by the limit overhang height when a φ6 mm micro-overhang test is performed. The limit overhang height in the φ6 mm micro-overhang test may be, for example, 1.65 mm or more, preferably 1.66 mm or more. The upper limit of the limit overhang height is, for example, about 2.0 mm or less. When the 0.2% proof stress is 300 MPa or more and the limit overhang height is 1.65 mm or more, the rivet part can be formed without breaking, cracking, or the like during the actual forming of the can lid while maintaining sufficient strength.

[0033] The structure and properties of the aluminum alloy sheet described above are those of a coated aluminum alloy sheet (precoated sheet) after painting and paint baking treatments are performed on a cold-rolled sheet (sheet after cold rolling). Note that such structure and properties may be those of an aluminum alloy sheet after heat treatment under specific conditions simulating paint baking treatment is performed on a cold-rolled sheet without painting and paint baking treatments or without forming into a can end. These structures and properties are the same or can be considered to be the same with only a slight difference if the conditions of the paint baking treatment and the heat treatment are the same.

[0034] The aluminum alloy coated sheet for can ends may be a precoated sheet having a resin layer provided on one or both sides of the aluminum alloy sheet. The resin layer may be a baked resin layer formed by applying an organic coating material such as an epoxy resin, a vinyl chloride resin, or a polyester resin, followed by heat treatment. The aluminum alloy sheet to which the organic coating material is applied may be a surface-treated aluminum alloy sheet that has been surface-treated or chemically treated with a surface treatment agent such as a chromate or zircon. The heat treatment temperature may be, for example, a temperature at which the peak metal temperature (PMT) is about 200°C or higher and 290°C or lower. The thickness of the resin layer may be, for example, about 0.5 μm or higher and 15 μm or lower.

[0035] The aluminum alloy coated sheet for can ends is formed into can ends, for example, as follows. The aluminum alloy coated sheet for can ends is blanked into a disk shape, and the blank material obtained is formed into a shell. A seaming portion for seaming with the can body is formed on the formed shell. The can end with the formed seaming portion is compound-lined by injecting rubber into the seaming portion. Then, the can end is formed into a can end through conversion forming, including a rivet forming process in which bubble forming is performed to protrude the center of the can end and button forming is performed to make the protruding portion a steep protrusion, a score forming process to perform groove processing on the opening, a bead embossing forming process to perform processing such as unevenness and letters, and a stake forming process to perform tab attachment. The can end formed in this way is seamed around a cylindrical can body with a bottom filled with the contents, and the aluminum can sealed with the can end is washed and sterilized.

[0036] Manufacturing method An example of a method for producing an aluminum alloy sheet constituting an aluminum alloy coated sheet for can ends will be described below. The method for producing an aluminum alloy sheet includes a casting step as a first step, a homogenization heat treatment step as a second step, a hot rolling step as a third step, and a cold rolling step as a fourth step, which are carried out in this order.

[0037] (1st to 3rd processes: casting process, homogenization heat treatment process, hot rolling process) The first step is to produce an ingot having a target composition by a semi-continuous casting method, and the second step is to perform a homogenization heat treatment on the aluminum alloy ingot produced in the first step.

[0038] In the first step, an aluminum alloy is cast by a semi-continuous casting method (DC (direct chill) casting) to obtain an ingot. Next, in the second step, a process of removing the region of the ingot surface that will become a non-uniform structure by facing and a process of performing a homogenization heat treatment are performed. This homogenization heat treatment is performed, for example, in the range of 400°C to 600°C, and also serves as preheating for the subsequent hot rolling.

[0039] The third step is hot rolling the aluminum alloy ingot that has been subjected to the homogenization heat treatment in the second step. The thickness of the hot-rolled plate obtained by hot rolling is usually set by calculating backward the total rolling reduction ratio by cold rolling from the thickness of the product plate obtained by cold rolling.

[0040] The coiling temperature, which is the end temperature of the hot rolling, is, for example, 300° C. to 370° C., preferably 320° C. to 370° C. When the coiling temperature is 300° C. or higher, the recrystallization rate of the hot-rolled sheet is improved, and the rivet formability of the aluminum alloy sheet after paint baking is further improved. On the other hand, when the coiling temperature is 370° C. or lower, the occurrence of a surface defect called seizure on the sheet surface is suppressed, and the properties of the sheet surface are improved.

[0041] The fourth step is a step of cold rolling the hot-rolled sheet obtained in the third step. In the fourth step, the hot-rolled sheet is cold-rolled without intermediate annealing to finish it into an aluminum alloy sheet of a predetermined thickness. The cold rolling is performed by setting multiple passes with a predetermined total rolling ratio so that the hot-rolled sheet is rolled to the thickness of the product sheet within an appropriate load range. Note that a pass refers to a single pass of the sheet between a pair of work rolls to be rolled.

[0042] The total rolling reduction ratio of the cold rolling is preferably 85.0% or more, and more preferably 90.0% or more. When the total rolling reduction ratio of the cold rolling is 85.0% or more, the strength of the aluminum alloy sheet is sufficient, and the dislocation density is increased, promoting the formation of subgrains after baking paint treatment. As shown in FIG. 1, the introduction of dislocations makes it easier for streaky dislocations to tangle, and many dislocation-dense regions 10 such as forest dislocations, cell walls, and shear bands are formed. Then, by the subsequent heat treatment such as baking paint, subgrains 20 are formed from the dislocation-dense regions 10, and the number of subgrains can be set within the range specified in the present invention. As a result, rivet formability tends to be improved.

[0043] In addition to setting the total rolling reduction ratio of the cold rolling to a predetermined range, it is preferable to set the sheet passing interval between the final rolling pass and the rolling pass immediately before it in the cold rolling to within 1.0 second, and the final coiling temperature after the final rolling pass to 135°C or higher. By setting the sheet passing interval to within 1.0 second, dynamic recovery in the final rolling pass is further promoted, the formation of subgrains is further promoted in the dislocation dense region, and more subgrains are formed than before during the paint baking in the next process. In addition, since the material temperature on the final pass inlet side is maintained high, the final coiling temperature after the final rolling pass can be set to 135°C or higher. This promotes static recovery of dislocations after coiling, and improves rivet formability due to an improvement in the work hardening index (n value). Furthermore, the rolling speed is improved without increasing the number of rolling passes in the cold rolling, so that productivity can be further improved. The range of the sheet threading interval is preferably within 0.80 seconds, more preferably within 0.50 seconds, and the range of the final coiling temperature is preferably 140° C. or higher, more preferably 150° C. or higher.

[0044] The aluminum alloy sheet produced by the above process is subjected to a chemical conversion treatment using a surface treatment agent such as a chromate-based or zircon-based agent. Then, an organic paint containing an epoxy-based resin, a vinyl chloride sol-based agent, a polyester-based agent, or the like is applied to form a coating film. The coating film thus formed is then subjected to a paint baking process at a PMT (Peak Metal Temperature) of about 200°C to 290°C, thereby producing a precoated aluminum alloy coated sheet for can ends. EXAMPLES

[0045] Although the embodiment of the present invention has been described above, examples in which the effects of the present invention have been confirmed will be specifically described below. Note that the present invention is not limited to these examples.

[0046] (Preparation of test materials) An aluminum alloy having the composition shown in Table 1 was cast by a semi-continuous casting method, and was subjected to facing and homogenization heat treatment by the methods shown as the first and second steps, and was hot rolled without cooling. The end temperature of the hot rolling was set to 300°C or more and 370°C or less as the coiling temperature. The obtained hot rolled sheet was then cold rolled under the conditions shown in Table 1 without intermediate annealing to obtain an aluminum alloy sheet as a cold rolled sheet with a sheet thickness of 0.25 mm. The balance of the composition shown in Table 1 is Al and unavoidable impurities. The cold rolling ratio is the total rolling ratio in cold rolling, and the sheet passing interval is the time required between the final rolling pass and the rolling pass immediately before it in cold rolling.

[0047] The aluminum alloy sheets thus obtained were then subjected to a distortion correction treatment and a chemical conversion treatment, after which an epoxy-based paint was applied thereto, and the sheets were baked in a continuous baking furnace at a PMT of 200° C. to 290° C. The baking temperature and baking time were the same in all of the manufacturing examples No. 1 to No. 12.

[0048] [Table 1]

[0049] The produced aluminum alloy coated sheets were used as test materials, and the number of subgrains, 0.2% yield strength, and limit overhang height (rivet formability) were measured by the following methods. The results are shown in Table 1. In Table 1, "-" indicates that the measurements were not taken.

[0050] Number of subgrains The structure of the center of each thickness in a plane parallel to the rolled surface of each test material was observed with a transmission electron microscope (TEM) at a magnification of 50,000 times to count subgrains and calculate the number of subgrains.

[0051] Specifically, the test material was mechanically polished to a thickness of 0.05 mm (0.1 mm) from the center of the plate thickness in both thickness directions, and then a twin-jet electrolytic polishing method was used to make a thin film with a thickness of 100 nm. This thin film was then examined with a transmission electron microscope at a magnification of 50,000 times to obtain a 205×10 -12 m2 The area was photographed. The number of subgrains measured within the photographed field of view was totaled to calculate the number of subgrains. Note that the number of subgrains was measured by taking into consideration the results of the rivet formability evaluation and selecting test specimens that clearly demonstrated the effects of the present invention. Note that there is no particular upper limit on the number of subgrains, but the upper limit is usually around 600.

[0052] Measurement of 0.2% proof stress For each test material, JIS No. 5 tensile test pieces were prepared with the tensile direction parallel to the rolling direction, and tensile tests were conducted according to the provisions of JIS Z2241. The plate thickness was calculated by subtracting the coating thickness from the plate thickness to obtain the 0.2% yield strength. The appropriate range for 0.2% yield strength is 300 MPa or more, and within this range, the pressure resistance strength of the lid is sufficient even for thin-walled can lids. There is no particular upper limit for 0.2% yield strength, but the upper limit is usually around 390 MPa.

[0053] Measurement of limit overhang height A 50mm x 50mm test piece was prepared from each test material, and an overhang test simulating the bubble process was performed to determine the limit overhang height. As shown in Figure 2, the overhang test was performed by sandwiching the test piece 1 between the upper and lower dies 2 and 3, fixing it with a certain blank holding force, and pressing the punch 4 vertically into the center of the test piece 1 to perform overhang processing. The dies 2 and 3 have an inner diameter of 6.60 mm and a shoulder radius of 0.40 mm, and the punch 4 has an outer diameter of 6.00 mm, a diameter of the central flat part of the head of 1 mm, and a shoulder radius of 2.50 mm. This overhang test measured the limit value (limit overhang height) of the overhang height at which the test piece 1 can be overhanged without cracking. The test was performed eight times with the same test material, and the average value of the six results excluding the maximum and minimum measurement results of the eight measurements was determined as the limit overhang height. The appropriate range of the limit overhang height was set to 1.65 mm or more. If the limit overhang height is 1.65 mm or more, a button of sufficient height can be formed during actual forming, the rivet formability is excellent, and the tab can be firmly fixed by the staking process. There is no particular upper limit for the limit overhang height, but the upper limit is usually around 2.0 mm.

[0054] As shown in Table 1, No. 1 to No. 12, in which the composition of the aluminum alloy coated sheet is within the range specified by the present invention, correspond to the examples because the number of subgrains is within the range specified by the present invention. In all of No. 1 to No. 12, the sheet passing interval between the final pass of cold rolling and the pass immediately before is within 1.0 second, the coiling temperature is 135°C or higher, and the limit overhang height (rivet formability) also reaches the acceptable value. In addition, as shown in FIG. 3, the limit overhang height and the final coiling temperature are in a proportional relationship, and the slope of the linear approximation line indicates that the final coiling temperature at which the limit overhang height is 1.65 mm or more is expected to be about 135°C. In addition, as shown in FIG. 4, the limit overhang height and the number of subgrains are in a proportional relationship, and the slope of the linear approximation line indicates that the number of subgrains at which the limit overhang height is 1.65 mm or more is expected to be about 45 or more. [Explanation of symbols]

[0055] 1 Test piece 2 Dice 3 Dice 4 Punch 10 Dislocation-dense region 20 Subgrain

Claims

1. An aluminum alloy plate comprising: Si: 0.05% by mass or more and 0.40% by mass or less; Fe: 0.05% by mass or more and 0.50% by mass or less; Cu: 0.01% by mass or more and 0.30% by mass or less; Mn: 0.10% by mass or more and 0.60% by mass or less; Mg: 4.0% by mass or more and 6.0% by mass or less; and the balance being Al and inevitable impurities; and a resin layer; The 0.2% yield strength is 330 MPa or more and the limit overhang height is 1.65 mm or more; In a plane parallel to the rolled surface, the structure of a region 50 nm thick in both thickness directions from the center of the sheet thickness is observed by a transmission electron microscope at 50,000 magnifications. -12 m 2 The coated aluminum alloy plate for can ends has a total of 45 or more subgrains in an area of ​​10 mm.

2. 2. The coated aluminum alloy sheet for can ends according to claim 1, wherein the aluminum alloy sheet contains Ti as an alloy component in an amount of 0.1 mass % or less.

3. 3. The coated aluminum alloy sheet for can ends according to claim 1, wherein the aluminum alloy sheet contains Cr as an alloy component in an amount of 0.1 mass % or less.

4. An aluminum alloy plate comprising: Si: 0.05% by mass or more and 0.40% by mass or less; Fe: 0.05% by mass or more and 0.50% by mass or less; Cu: 0.01% by mass or more and 0.30% by mass or less; Mn: 0.10% by mass or more and 0.60% by mass or less; Mg: 4.0% by mass or more and 6.0% by mass or less; the remainder being Al and unavoidable impurities; and a resin layer; A method for producing a coated aluminum alloy sheet for can ends, the method comprising the steps of: (a) observing a structure of a region 50 nm thick from the center of the sheet thickness in both thickness directions in a plane parallel to the rolled surface with a total of 45 or more subgrains in an area of ​​205×10 −12 m 2 as observed with a transmission electron microscope at 50,000 magnification; The method includes a casting step, a homogenization heat treatment step, a hot rolling step, and a cold rolling step in this order, The method for producing a coated aluminum alloy sheet for can ends, wherein in the cold rolling step, a final coiling temperature is 135° C. or higher.

Citation Information

Patent Citations

  • High-strength high-moldability hard aluminum alloy sheet and its production

    JP1988293144A

  • Aluminum plate for automobile parts and its manufacture

    JP1993140687A

  • Aluminum alloy sheet for packing container tab, and production method therefor

    JP2005200754A

  • Aluminum alloy sheet for can-top

    JP2016079501A

  • Aluminum alloy sheet for can top

    JP2017066430A